Reply to Martin Glaberman - Ignatiev, Noel (Labour / Le Travail, 1995)
A chapter of the book "Labour/Le Travail" is presented. It highlights the objective why people deny the proletarian character of slaves. It examines the relationship between history and politics. It mentions the attempt of the governments to establish universal suffrage and universal arming of the people.
Keywords: History; LABOUR/LE Travail (Book); PRACTICAL politics; PROLETARIAT; SLAVES; Working class